PENGEMBANGAN VIDEO MEDIA PEMBELAJARAN MATEMATIKA DENGAN BANTUAN POWTOON - Ridha Yoni Astika; Bambang Sri Anggoro; Siska Andriani (Jurnal Pemikiran dan Penelitian Pendidikan Matematika (JP3M), 2019)
This research is a development research aimed at developing powtoon-assisted learning media, knowing student responses, and effectiveness. The procedure in this development uses a 4-D development model, namely: Define, Design, Develop, and Disseminate. The product developed was in the form of a learning media video on a two-variable linear equation system material for VIII grade students. The instruments used in this study are learning media assessment sheets by experts to measure the validity of learning media, student response questionnaires to measure the attractiveness of learning media, as well as learning outcomes tests to measure the effectiveness of the use of instructional media.